2004
DOI: 10.1210/er.2003-0029
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and Overlapping Combinatorial Codes Orchestrate Hormonal Responsiveness and Dictate Cell-Specific Expression of the Genes Encoding Luteinizing Hormone

Abstract: Normal reproductive function in mammals requires precise control of LH synthesis and secretion by gonadotropes of the anterior pituitary. Synthesis of LH requires expression of two genes [alpha-glycoprotein subunit (alphaGSU) and LHbeta] located on different chromosomes. Hormones from the hypothalamus and gonads modulate transcription of both genes as well as secretion of the biologically active LH heterodimer. In males and females, the transcriptional tone of the genes encoding alphaGSU and LHbeta reflects dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 170 publications
0
85
0
Order By: Relevance
“…The role of the CRE in mediating aGSU transcription is well characterised (Heckert et al 1996, Burrin et al 1998), and we have previously shown an altered response to cAMPmediated transcription of the human aGSU promoter between aT3-1 and LbT2 cells (Fowkes et al 2003). In our current study, CNP was able to significantly stimulate the proximal K244 bp construct of the human aGSU promoter in LbT2 cells, which is known to contain a tandem CRE, the gonadotroph-specific element that binds SF-1, and a consensus GATA site , Jorgensen et al 2004. Of these sites, the CREs are potential targets for CNP action, given that cGMP is able to enhance CREB phosphorylation (Lu & Hawkins 2002).…”
Section: Discussionmentioning
confidence: 59%
“…The role of the CRE in mediating aGSU transcription is well characterised (Heckert et al 1996, Burrin et al 1998), and we have previously shown an altered response to cAMPmediated transcription of the human aGSU promoter between aT3-1 and LbT2 cells (Fowkes et al 2003). In our current study, CNP was able to significantly stimulate the proximal K244 bp construct of the human aGSU promoter in LbT2 cells, which is known to contain a tandem CRE, the gonadotroph-specific element that binds SF-1, and a consensus GATA site , Jorgensen et al 2004. Of these sites, the CREs are potential targets for CNP action, given that cGMP is able to enhance CREB phosphorylation (Lu & Hawkins 2002).…”
Section: Discussionmentioning
confidence: 59%
“…Of note, it is known that estrogen (E2) inhibits expression of the TSH gene (Cohen and Wondisford, 2005) at the transcriptional level, although its magnitude is smaller than that by T3. E2 is also known to reduce expression of the GSU gene (Chaidarun et al, 1994;Shupnik et al, 1988), the promoter of which has a functional GATA-RE (Jorgensen et al, 2004;Steger et al, 1994). In agreement, the serum level of TSH in women has a tendency to elevate after the menopause (Nagayama et al, 2008).…”
Section: Ligand/receptor Specificity In Negative Regulation Of the Tsmentioning
confidence: 82%
“…6). This notion is supported by the observation that T3/TR 2 inhibits GATA2-induced activation of the GSU promoter and the endothelin-1 (ET-1) promoter, both of which are known to bear a functional GATA-RE (Jorgensen et al, 2004;Steger et al, 1994;Dorfman et al, 1992). In addition, T3/TR inhibited the CD34 gene-derived GATA-RE fused to a heterologous thymidine kinase promoter (Matsushita et al, 2007).…”
Section: T3/tr Represses Gata2-dependent Activation Of the Tshβ Promomentioning
confidence: 95%
“…Substantial progress has been made in the identification of the transcription factors that are required for basal, tissue-specific and GnRH-activated expression of the Lhb subunit gene. In the highly conserved proximal 140 bp Lhb promoter region, several specific cis-acting regulatory elements were found to interact with trans-acting early growth response protein 1, the orphan nuclear receptorsteroidogenic factor 1 (SF1) -and a paired-like homeodomain protein PITX1, whereas regulatory elements for SP1 protein and CArG box were identified in the distal domain of the rat sequence (Jorgenssen et al 2004). PITX1 exerts an essential role not only throughout pituitary development (Szeto et al 1996, Kurowani et al 1999, but also in postnatal life, when it regulates several pituitary-specific genes through direct interaction with other specific transcription factors (Tremblay et al 1998(Tremblay et al , 2000.…”
Section: Introductionmentioning
confidence: 99%